Consultease V2: redefining consultancy management for academics - Ab Rahman, Liyana; Alwi, Fatimah; Ahmad, Mahfuzah; Shamsudin, Siti Marlia (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
University lecturers have multiple number of responsibilities with the main responsibilities are teaching and learning. Research and publication are also vital as these provide positive attributes to the quality of teaching and learning. Recently, consultancy work has become increasingly important as universities may strengthen ties with industries and be less independent on government grant or budget. However, the lack of a dedicated digital solution has caused an inefficiency in the management of consultancy work. Unlike teaching, there are several platforms that support teaching and learning activities such as u-Future, and Google Classroom. The unavailability of any application that aids consultancy work has caused lecturers to use several platforms. This may lead to missed deadlines and disorganized documentation. Thus, this project proposes a specialized mobile and web-based application to organise consultancy work at one stop. The useful features of Consultease V2 are task tracking, document storage, automated reminders, announcement postings, and meeting scheduling. As a result, this application offers an integrated task management system and structured document storage which will enable lecturers to manage multiple projects efficiently, ensure data securities and access control mechanisms. Other than lecturers, universities and research institutions are also benefit from Consultease V2. Not only enhancing the efficiency of consultancy work among the lecturers, Consultease V2 also allows universities and research institutions reap financial benefits via the commercialisation of the intellectual property of Consultease V2.